CIRCADIAN CHANGES IN THE ANTICOAGULANT EFFECT OF HEPARIN. PHARMACODYNAMIC AND PHARMACOKINETIC EFFECT - Decousus, H A; Scully, M F; Reynaud, J; Arnaud-Crozat, E; Boissier, C; Barral, R; Queneau, P; Reynaud, J; Parker, C; Kakkar, v v (Thrombosis and Haemostasis, 1987)
Six patients, with thromboembolic arterial disease, were prospectively studied to assess the influence of the time of injection of a constant dose of calcium heparin (Choay ), given subcutaneously, on the level of heparin measured by APTT and anti-Xa assay. For each patient, the initial dose of heparin was adjusted by APTT 6h after a morning injection to 1.5 and 2.5 times control. Dose was then kept constant. Four randomized times of injection were tested (8am, 4pm, 8pm and 12pm), in each patient acting as his own control. Blood was sampled via a cannula, at Oh, 2h, 3h,4h,5h,6h, 8h, lOh and 12h after injection. The mean APTT and anti-Xa values for the evening injections (8pm and 12pm) were higher than for the morning injection (8am), at 2h until lOh after injection. These differences were significant (analysis of variance:p<0.001) and reached almost 30 seconds for mean APTT values measured 4h, 5h and 6h after injection. For the afternoon injection (4 pm) the mean APTT and anti-Xa values were intermediate but significantly different from all the other times of injection (analysis of variance: p<0.01).Blood was sampled also on two consecutive days at 12am and 12pm from eight patients receiving heparin subcutaneously for treatment of DVT (administered at 6am and 6pm respectively). Heparin levels by APTT, TT and three antifactor Xa methods (Heptest, Hepaclot, Chromogenic) were significantly higher at night than morning (analysis of variance p<0.005). Cosinor analysis confirmed these results are consistent with circadian variation as we have previously reported after continuous infusion of UF heparin (Br. Med. J., 1985, 290, 341-344). The observed variation was found to be a resultant of a pharmacodynamic effect (circadian variation in assay response to heparin) and pharmacokinetic effect (circadian variation in 99m Tc-heparin clearance). Such circadian variation should be taken into account when deciding heparin dosage.